Maternal body condition : effect on time of calving, offspring survival and body weight in reindeer - Korpinen, Caroline (SLU/Dept. of Animal Nutrition and Management (until 231231), 2017)
The reindeer husbandry faces many challenges and one of the most crucial is the high calf mortality. As some reindeer herding districts have their calving grounds based in the forest, they are at high risk of losing a large number of the calves each season to brown bear predation as the bears also rely heavily on the forest as their natural habitat. To find a solution to the problem, the Swedish government commissioned a study in 2009 with the objective to evaluate and develop different measures to prevent predator damage on reindeer. Udtja- and Gällivare forest reindeer herding districts were chosen to be part of the project as both districts suffer from a high (40 % respectively 60 %) calf mortality where a significant part is caused by bear predation. One aspect of this study was to further investigate one of the preventive measures developed in the bigger project, keeping females enclosed during the calving period (end of April until beginning of June). However, emphasis in the present study was to highlight the importance of female nutrition (measured as body mass prior to calving) on the calf. The study focused on three main questions; 1) To what extent does the weight of the dam in spring affect the calf weight? 2) Is calving date related to the dams’ body weight in spring, before calving? 3) Does the weight of the dam affect the early survival of the calf? The study also aimed to study potential differences and similarities among the four different groups of reindeer, comparing two years in Gällivare (two groups 2015 and one group 2016), and the two herding districts, Udtja and Gällivare studied in 2016. In this study data from two years, 2015 (two groups of reindeer in Gällivare) and 2016 (one group in Gällivare and one in Udtja) was used. The females used in the study (107-225 females per group) were weighed and tested for pregnancy in April. Only pregnant females were included in the study. They were then put inside the enclosure and were fed additional feed until the beginning of June when the ...